Indonesian Government Policy Guidelines; Implementation of Fit For 55 Policy, Emission Trading Systems, and Fuel Quality Directive Based on TBT Agreement - Salwa Salsabila; Atip Latipulhayat; Garry Gumelar (Institut Agama Islam (IAIN) Kendari, 2024)
The European Green Deal is a strategic initiative from the European Union which aims to make the European Union carbon neutral by 2050. One of its main commitments is to reduce greenhouse gas emissions by 50 to 55 percent by 2030, compared to 1990. The TBT Agreement regulates such that regulations, standards, testing techniques and certification procedures at the domestic level do not constitute obstacles to international trade. Standards in the biofuel trade have an important role in the manufacturing industry, apart from that they greatly influence the sales of a product in national and international markets. The Indonesian government has taken steps to address these environmental concerns through the development and strengthening of Indonesian Sustainable Palm Oil (ISPO) certification. This certification aims to increase sustainability in the palm oil industry by implementing standards that ensure palm oil production is carried out in a way that minimizes environmental impacts, protects peatlands, reduces greenhouse gas emissions, and improves the social conditions of workers and local communities.